Implementing Sino-Russian Educational Programs for Training Chinese Engineers - Nina L. Fedotova; Elena B. Solovyeva; Victor B. Vtorov; Lyudmila G. Yun (National Research Mordova State University, 2019)
Introduction. The relevance of this study is determined by the gradual expansion of contacts between the PRC and the Russian Federation in the educational sphere and the need to improve the national education systems. The purpose of the article is to identify methodological problems in organizing Sino-Russian educational programs for training engineers for the People's Republic of China and to propose the optimal solution to these problems. Materials and Methods. In considering the problems of organization of the educational process for joint Sino-Russian educational programs, we use empirical methods: description, content analysis, comparison and synthesis. A survey of teaching staff and students was conducted. Students and teachers, who took part in the joint program of Saint Petersburg Electrotechnical University and Xuzhou University of Technology were selected to be interviewed. The survey also involved teaching staff and students of Jiangsu Pedagogical University. Results. We will suggest recommendations for the development of joint programs, the purpose of which is to prepare highly qualified engineers for the People's Republic of China. These recommendations will improve the educational process, the quality of the professional training of Chinese students, enhance their level of proficiency in the Russian language. Our results suggest that to improve the quality of training of Chinese engineers who receive two diplomas, it is necessary to take into account the motives of Chinese students, their cognitive style of learning, the used learning strategies and the national characteristics of the Chinese education system. Discussion and Conclusion. The results of this study may be useful to educators involved in collaboration activities between educational institutions of different countries. Following the proposed recommendations, we expect teachers in special subjects to easily write textbooks, including digital ones that suit the topical students' needs and enable teaching staf f efficiency.